The Effect of Service Quality on Customer Satisfaction at Roti Bakar 88 Poris Tangerang - Sembiring, Vienna Artina; Prabandari, Wijayanti Dewi; Darsiah, Anis (Institut Pariwisata Trisakti, 2022)
This study aims to determine the effect of service quality on customer satisfaction. This type of research is descriptive quantitative research with simple regression. The population in this study were all consumers who visited Roti Bakar 88 Poris Tangerang, while the sample in this study amounted to 99 respondents. The sampling technique in this study used accidental sampling. Data collection techniques by distributing questionnaires. The results showed that service quality had a significant effect on customer satisfaction. This is because the Roti Bakar 88 Poris Tangerang has adequate physical evidence, adequate performance, consumers do not wait too long for food to be consumed, responsiveness is very fast and alert in helping what consumers need, guarantees that can provide a sense of security in the process. Use services and empathy that can provide comfort by giving personal attention to customers. Roti Bakar 88 Poris Tangerang continues to be the attention of consumers because of its best service quality. It always maintains the atmosphere in the restaurant in a calm and conducive condition, especially when it is crowded, so that consumers are happy to linger at Roti Bakar 88 Poris Tangerang to create a sense of customer satisfaction and a sense of Loyalty. Keywords: Service Quality, Customer Satisfaction